Efecto de la harina de zapallo (Cucurbita maxima) y probióticos en lechones en etapa inicial - Castro Guerrero, Luisa Fernanda (2025)
The objective of this study was to evaluate the effect of a diet supplemented with pumpkin flour (Cucurbita maxima) and probiotics on the productive performance of pigs in the initial growth stage. Two experimental groups were used: a control group fed a conventional basal diet and a treated group that received the same diet supplemented with 5% pumpkin flour and a multistrain probiotic consortium. During the experimental period, weekly body weight, cumulative weight gain, and feed conversion ratio were recorded. Although no statistically significant differences (p > 0.05) were detected in average weekly body weight between treatments, the pigs in the supplemented group showed a higher cumulative gain of 2.88 kg, representing a biologically relevant outcome during this critical development stage. Regarding feed conversion, statistically significant differences (p < 0.05) were observed in favor of the treated group, indicating greater efficiency in feed utilization. These findings suggest that including pumpkin flour and probiotics in the diet can improve nutritional uptake and promote the growth of pigs during the initial stage, contributing to productive performance and the profitability of pig production systems.